(untitled) (REMUNOM, 2024)
This study addresses the contributions of psychologists in the context of emergencies and disasters, events that generate material, environmental and, above all, human damage. It aims to present the main contributions of the Psychologist in the context of emergencies and disasters, to act from the perspective of comprehensive crisis management, in accordance with the guidelines of the Federal Council of Psychology. To this end, bibliographical research was carried out, descriptive in terms of purposes and qualitative in terms of approach to the problem. Literature findings indicate that with the increase in catastrophic events in Brazil and around the world, the intervention of psychology has become vital and has expanded its field of action together with other social actors. In this context, early psychological care is essential to provide immediate support and prevent more serious problems. The RAPID model clearly and practically structures the intervention, ensuring the organization and effectiveness of initial support, promoting resilience in communities while preparing for the transition, if necessary, to specialized mental health services. We can affirm the importance of the psychologist’s work in line with public policies as an indispensable part of this process before, during and after the disaster. However, it also highlights the need for more studies and research in this area, as despite the relevance of the topic, the subject is still little covered compared to other topics related to psychology.